O agir de tutores na EAD: “minha experiência na tutoria me permite dizer...” - Nelo, Maria Jaberlânye da Silva (2017)
Concurrently with the expansion of the e-learning mode, the need to expand studies focused on the tutoring activity arises. Playing an extremely important role in online educational setting, the tutor crosses impasses that, in many cases, generate doubts and insecurity about the role they play. Thus, this research aims to investigate the representations of acting of elearning tutors on the work they develop, in order to verify the tutor social function, based on the texts/speeches produced by them and the prescriptive documents of this activity. Based on the theoretical contributions of Socio-Discursive Interacionism (SDI) from Bronckart (2012/1999, 2007, 2006); Machado (2004, 2007); Abreu-Tardelli (2004); Pereira, Medrado and Reichmann (2015), and in the work sciences with Amigues (2004); Saujat (2004); Clot (2007, 2010); Nouroudine (2002), we understand that action and language play a fundamental role in human development, so it is possible to understand from the view of the tutors themselves, coming from different fields of knowledge, and the functions they perform in their professional activity, the place they occupy in society. To better understand this multiplicity of knowledge that involves the activity of tutoring in e-learning, we analyzed prescriptive documents of the tutorial activity, texts produced in the discussion forums of an online training course offered to tutors from selective processes and texts/speeches generated from semi-structured interviews. The analysis showed that the modalizations present in the texts/speeches produced by the tutors are characteristics of professionals responsible for their actions, and that despite non-experience, or lack of prescriptions, they are able to conduct their work based on what they can and should do. The representations about teaching activity in e-learning found, lead us to a conception that there is still an (mis) understanding about the tutor's work. Under the Brazilian legislation, the mentions to these professionals are still few and vague. In the forum posts of the training course we observe that the representations of each collaborator converge in some aspects, but in others there are disagreements, especially with regard to the duties to be performed by the tutor. In the interviews, we observed that the representations of the tutors are anchored mainly in the previous experiences they had with elearning, which gave rise to the various duties of the tutor, some of them, absent in the prescriptive documents themselves.